(8y+4)+(4y+8)=5y-9

Simple and best practice solution for (8y+4)+(4y+8)=5y-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8y+4)+(4y+8)=5y-9 equation:


Simplifying
(8y + 4) + (4y + 8) = 5y + -9

Reorder the terms:
(4 + 8y) + (4y + 8) = 5y + -9

Remove parenthesis around (4 + 8y)
4 + 8y + (4y + 8) = 5y + -9

Reorder the terms:
4 + 8y + (8 + 4y) = 5y + -9

Remove parenthesis around (8 + 4y)
4 + 8y + 8 + 4y = 5y + -9

Reorder the terms:
4 + 8 + 8y + 4y = 5y + -9

Combine like terms: 4 + 8 = 12
12 + 8y + 4y = 5y + -9

Combine like terms: 8y + 4y = 12y
12 + 12y = 5y + -9

Reorder the terms:
12 + 12y = -9 + 5y

Solving
12 + 12y = -9 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
12 + 12y + -5y = -9 + 5y + -5y

Combine like terms: 12y + -5y = 7y
12 + 7y = -9 + 5y + -5y

Combine like terms: 5y + -5y = 0
12 + 7y = -9 + 0
12 + 7y = -9

Add '-12' to each side of the equation.
12 + -12 + 7y = -9 + -12

Combine like terms: 12 + -12 = 0
0 + 7y = -9 + -12
7y = -9 + -12

Combine like terms: -9 + -12 = -21
7y = -21

Divide each side by '7'.
y = -3

Simplifying
y = -3

See similar equations:

| 15x(y-2)= | | 15x(y-2)=40 | | -72=6x-3(-7x-21) | | -16t^2+22t+22=0 | | 9x+2=15x | | 1/4+3/4t=10 | | 1.3x-2.39=5.76x+4.47 | | 7x^3+22x^2+17x+2=0 | | 2x+3y=79 | | 7500=x*.5+x*.5 | | 1/6f+3/4=1/2 | | 2x+39b=14+3b | | 2v-6=-2v+6+7-3 | | 6(-3-7)= | | X+(x*0.087)=y | | 9y+6(4y-3)=5(y-7) | | 32w^2+32w+8=0 | | 1/3w9 | | 6u+8v-7-6u-4v+8w= | | -4(1+b)+8b=-14+2b | | -192=8(4x-8) | | x^2=x-57 | | 15/50=3x | | 5x(x+3)+6(x+3)= | | 6(k+7)=18+2k | | -9/4=r-4/5 | | 8x+4(x-7)=3(8-x)+12 | | 3c+7+12c=53 | | 32+n+n=126 | | 36x^2y-18xy^2+2y^3= | | -31/2x=14 | | m-5m-8=3+(-7)+m |

Equations solver categories